Method development and application for the analysis of chiral organic marker species in ice cores - J. Schäfer; A. Beschnitt; F. Burgay; F. Burgay; T. Singer; T. Singer; T. Singer; M. Schwikowski; M. Schwikowski; M. Schwikowski; T. Hoffmann (Atmospheric Measurement Techniques)
Glaciers are valuable environmental archives that preserve organic compounds from atmospheric aerosols that can be used as marker species for their respective emission sources. Most environmental studies do not distinguish between the enantiomers of chiral compounds, although these compounds, mostly from biogenic sources, are very common in the atmosphere. We have developed a two-dimensional (2D) liquid chromatography (mLC–LC) method that allows the simultaneous determination of the chiral ratios of the monoterpene oxidation products cis-pinic acid and cis-pinonic acid in ice-core samples. The method combines a reversed-phase column in the first dimension and a chiral column in the second dimension in a simple instrumental setup with only one additional six-port valve. This novel method was successfully applied to selected ice-core samples from the Belukha Glacier in the Siberian Altai spread over the period 1870–1970 CE. The chiral ratio of cis-pinic acid showed fluctuating values, while the chiral ratio of cis-pinonic acid remained more constant with an excess of the (−)-enantiomer.